Navigating Uncertainty: Sensemaking of Technological Change in the Rally Industry - Könönen, Christa (2025)
The automotive industry is currently undergoing a global technological change, seeking new directions for future powertrain technologies. This change is driven by increasing sustainability pressures, regulatory developments, and societal expectations, all forcing industry actors to navigate an environment marked by high uncertainty. Within this context, this study explores how actors in the rally industry perceive, interpret, and make sense of technological change in a situation where future direction remains open. This study is based on the principles of grounded theory, in which theoretical understanding is developed inductively from empirical data. This is a qualitative study based on insights gathered from interviews conducted with actors in the rally industry. The interviews were analyzed using the Gioia method, which proceeds through a systematic, three-level coding structure. The findings reveal that the cognitive processes of industry actors in the context of technological change are characterized by two interrelated key dynamics. The first process concerns the acceptance of change and the various adaptation strategies that actors adopt in response. The second process relates to how actors navigate conflicting demands, which leads actors to engage in paradoxical thinking. The interplay between these two processes forms a comprehensive picture of how actors interpret technological change and position themselves with it. Understanding these dynamics helps to explain why actors adopt differing approaches in the context of technological change.